The question harmonise business and government under tax reform - Боднар, Г. Ф. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
The article presents the theoretical and practical aspects of interests’ harmonization between a business and the government in terms of tax reform and its influence on the contemporary economic situation in Ukraine. The research actuality in the conditions of economic crisis is justified. The main directions of improving the functioning of the tax reform mechanism in domestic practice are highlighted.